1983
DOI: 10.1021/i100012a007
|View full text |Cite
|
Sign up to set email alerts
|

New model of micromixing in chemical reactors. 1. General development and application to a tubular reactor

Abstract: A new model of turbulent mixer based on the spectral interpretation of mixing in an isotropic homogeneous turbulent fieid is developed and used in interpreting micromixing of the liquid phase in homogeneous chemical reactors. The liquld content of a reactor is divided into two zones: the zone of complete segregation and the zone of molecular dissipation of concentration fluctuations. Reduction in size of completely segregated liquid elements forming the first zone, large-scale eddies, is related to the mixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In this report we wish to interpret the plume length measurements of Rice et al (1964) and Pohorecki and Baldyga (1983) from a fundamental viewpoint, starting with the probability density function (PDF) method (Toor, 1962) which, for the conditions of the experiments, will be seen to reduce to Danckwerts' (1957) result. We do not include the measurements of Kristmanson and Danckwerts (1961) because of uncertainties raised by their use of a two-color indicator and a weak base.…”
mentioning
confidence: 99%
“…In this report we wish to interpret the plume length measurements of Rice et al (1964) and Pohorecki and Baldyga (1983) from a fundamental viewpoint, starting with the probability density function (PDF) method (Toor, 1962) which, for the conditions of the experiments, will be seen to reduce to Danckwerts' (1957) result. We do not include the measurements of Kristmanson and Danckwerts (1961) because of uncertainties raised by their use of a two-color indicator and a weak base.…”
mentioning
confidence: 99%
“…However, in this case different turbulence model seem to affect the predicted plume length, as shown in Figure 10. [24]. The model results reported by Hjertager et al [15] are also shown for comparison.…”
Section: Wallmentioning
confidence: 87%
“…Figure 9 Second tubular reactor plume length computed using various TKI models with 𝜅 − 𝜖 model vs. the experimental values in [24]. The model results reported by Hjertager et al [15] are also shown for comparison.…”
Section: Wallmentioning
confidence: 96%
See 1 more Smart Citation
“…Lamellar mixing models provide an alternative approach to modeling the complex interactions between local motion, molecular diffusion, and chemical reaction in the mixing of miscible reactive fluids. Pohorecki and Baldyga (1983a, b) proposed using the spectral interpretation of mixing in an isotropic turbulent field in order to explain micromixing effects in homogeneous liquid phase chemical reactors. The authors in their further work ( 1 9 8 3~) used the same model to evaluate the influence of the intensity of mixing on the rate of precipitation in an agitated, perfectly macromixed vessel.…”
Section: Diflusion Modelsmentioning
confidence: 99%